Outcome of Circumcision Timing and its Effect on Infants and Preschool Age Children Morbidity - Obaid , Kareem Assi (Diyala Journal of Medicine, 2019)
Background: Circumcision is a common procedure, but regional and societal attitudes differ on whether there is a need for a male to be circumcised and if so, at what age, sexually transmitted diseases, penile cancer, and phimosis and a reduction in the incidence of human papilloma virus related cervical cancer in female sexual partners. This is an important issue for many parents, but also pediatricians, other doctors, policy makers, public health authorities, medical bodies, and males themselves. Worldwide 1 in 3 males are circumcised, totaling an estimated 1.2 billion. The largest number of circumcised males are Muslims (approx. 70% of circumcised males globally). Objectives: The objective of the study is to find whether there is difference in morbidity factors like infections, hospital admissions, complications, and growth and circumcision complications in between preschool age children with different timing of circumcision. Method & Materials: This study is a cross sectional study done in Albetool Maternity Hospital in Diyala province of Iraq between October 2012 and March 2013 .This study is looking for children who were circumcised and age of circumcision and complained from urinary tract infection before and after circumcision and other complication of circumcision. Results: Of one hundred of cases included in the study where we found that 26 ( 26%) of circumcised male were delivered by caesarian section and 74 ( 74 %) normal delivery, 81 (81 %) without family history of recurrent UTI, 26 (26 %) with family history of UTI , 93 (93 % ) without UTI &sepsis after circumcision, 7( 7% ) with UTI and sepsis after circumcision , 92 (92 %) without urinary catheterization, 8 (8 %) with urinary catheterization , 12 (12% ) hospital circumcision and 88 (88 % ) home circumcision, 59 (59 % ) breast feeding, 49 (49 %) bottle feeding, 66 ( 66 %) infants and 44 ( 44 % ) preschool age and 26 (26% ) with UTI and sepsis before circumcision and 48 (48 %) without UTI and sepsis before circumcision. Conclusion: Health benefits include protection against urinary tract infection and thus prevent permanent damage to the still-growing kidney, reduced likelihood of penile inflammation, and elimination of risk of phimosis.